HUBUNGAN SIKAP KERJA DENGAN KELUHAN NYERI PUNGGUNG BAWAH (LOW BACK PAIN) DAN TINGKAT NYERI PADA TUBUH PADA PENENUN DESA PRINGGASELA KABUPATEN LOMBOK TIMUR - Arham, M. Zawwil; Sucipta Putri, Wayan Citra Wulan (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 3 (2023): Desember 2023DO - 10.24843/ACH.2023.v10.i03.p12, 2023)
Pringgasela village has about 420 weavers, information was obtained from one of the weavers in Pringgasela that what the weaver felt at that time was feeling aches and pains in the arms, shoulders, and lower back to the back of the thighs. If the work attitude is not ergonomic, it can cause complaints of low back pain and the level of pain in the body. The purpose of this study was to determine the relationship of work attitudes towards complaints of low back pain and the level of pain in the body in Pringgasela Village weavers. This research is an analytical observational study with a quantitative approach using a cross-sectional design. The respondents to this study were 80 people who were selected through accidental sampling techniques. The data were tested with chi-square analysis. The results showed that 23.75% of weavers experienced mild LBP complaints and 76.25% of weavers experienced severe LBP complaints. Meanwhile, weavers identified low body pain levels of 55% and high levels of 45%. Meanwhile, weavers who have a low work attitude amount to 58.75% and high to 41.25%. There was no meaningful relationship between work attitudes (p=0.931) and complaints of low back pain. There is a meaningful relationship between work attitudes (p=0.019) and the level of pain in the body towards Pringgasela Village weavers. It is recommended to weavers to adjust the attitude of work when weaving, as well as regular rest. Keywords: Work Attitude, Low Back Pain, Body Pain Level, Weaver.